SAE Technical Paper Series 2002
DOI: 10.4271/2002-01-2729
|View full text |Cite
|
Sign up to set email alerts
|

Parameterization and Transient Validation of a Variable Geometry Turbocharger for Mean-Value Modeling at Low and Medium Speed-Load Points

Abstract: The parameterization of variable geometry turbochargers for mean-value modeling is typically based on compressor and turbine flow and efficiency maps provided by the supplier. At low turbocharger speeds, and hence low airflows, the heat exchange via the turbocharger housing affects the temperature-based measurements of the efficiencies. Therefore, the lowspeed operating regime of the turbocharger is excluded from the supplied maps and mean-value models mainly rely on extrapolation into this region, which is re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(41 citation statements)
references
References 10 publications
0
38
0
2
Order By: Relevance
“…The geometrical turbocharger characteristics, mainly the distance between compressor and turbine, appear to influence greatly the heat fluxes. More recently, in 2002, Jung et al [6] suggest a parameterisation of turbine maps to obtain the behaviour of the turbine in its actual environment. They study heat losses considering the turbine as an exchanger which efficiency is derived from the manufacturers map.…”
Section: Bibliography Surveymentioning
confidence: 99%
“…The geometrical turbocharger characteristics, mainly the distance between compressor and turbine, appear to influence greatly the heat fluxes. More recently, in 2002, Jung et al [6] suggest a parameterisation of turbine maps to obtain the behaviour of the turbine in its actual environment. They study heat losses considering the turbine as an exchanger which efficiency is derived from the manufacturers map.…”
Section: Bibliography Surveymentioning
confidence: 99%
“…Usually the pressure drops across the coolers are neglected, and the temperatures after the coolers can be calculated by the following equations [16]:…”
Section: Coolersmentioning
confidence: 99%
“…When considering experimental results by [109,126,127] it is assumed that the turbine efficiency can be presented, with pressure ratio on the x-axis, by plotting curves for each speed line which goes through the point of maximum efficiency. The efficiency can be modelled as a parabolic function of the blade speed ratio [125,127,128,140]: From the above it is concluded that from a basic turbine map the turbine efficiency can be calculated as a function of pressure ratio and speed with the use of the blade speed ratio.…”
Section: Turbinementioning
confidence: 99%